Research on spanish heraldry, with special atten-tion to the early modern age. State of affairs - Valle Porras, José Manuel (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
This article aims to contribute to a better knowledge of the research on Spanish heraldry to date. It also attempts to help achieve two important goals. First, the mutual approach between heraldists and historians –especially of the nobility–, and between the latter and the coats of arms as an object of study. Second, we want to emphasize the need to encourage research on Heraldry in the Early Modern Age, a period much more neglected than the medieval one. For these purposes we have organized this paper into three main sets: (a) the explanation of the main trends found in the research on coats of arms, (b) the review of the most outstanding contributions made by heraldry, on the one hand, and by the historiography of the nobility, on the other, for both the Middle Ages and the Early Modern age –separately– in our country, and finally (c) a proposal to develop lines of research in the study of the coats of arms between the 16th and early 19th centuries.